Factors Driving Interest in Saving at Bank Syariah Indonesia (BSI) - Fiqi Diyah Sulistyowati,; Agus Setiawan, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2025)
Bank Syariah Indonesia (BSI) is the largest Islamic bank in Indonesia, but people's interest in saving at BSI is still relatively low. This condition raises questions about the main factors that affect people's interest in saving. This study aims to analyze the influence of trust, promotion, religiosity, brand image, and social environment on people's interest in saving in Polokarto District, Sukoharjo Regency. The method used is a quantitative approach with a non-probability sampling technique through quota sampling and data processing using SPSS. Research results show that promotion, brand image, and social environment have a significant effect on interest in saving, while trust and religiosity do not have a significant effect. These findings highlight the importance of social aspects and communication strategies in shaping people's financial behavior, especially in communities with strong social interactions. This study contributes to Islamic financial institutions to adjust marketing strategies that not only emphasize religious values, but also community-based approaches. These findings also serve as a reference for policy makers in encouraging contextual-based Islamic financial inclusion. The limitations of this study lie in the limited geographical scope and variables, so further research is recommended to cover a wider area and other relevant variables.